Acute Necrotizing Encephalopathy of Childhood: Correlation of MR Findings and Clinical Outcome - Wong, A.M.; Simon, E.M.; Zimmerman, R.A.; Wang, H.-S.; Toh, C.-H.; Ng, S.-H. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: The clinical outcome of acute necrotizing encephalopathy of childhood (ANEC), an encephalopathy characterized by symmetrical involvement of the thalami, has historically been poor, but recent studies have reported better outcomes. By devising a MR imaging scoring system, we determined the relationship between characteristic MR findings and clinical outcome of patients with ANEC.METHODS: MR studies of 12 patients with ANEC were retrospectively reviewed. A MR imaging score was calculated for each patient according to the presence of hemorrhage, cavitation, and location of lesions. Clinical outcome of the patients was assessed, yielding outcome categories based on health state utility value. Spearman rank test was used to correlate the MR imaging score with clinical outcome of the patients.RESULTS: Statistically significant correlation (r = 0.76, P = .001) was found between the MR score and the outcome category. The thalami were involved in all 12 patients, brain stem in 10, cerebral white matter in 8, and cerebellar white matter in 4. Hemorrhage was present in 5 patients and cavitation in 4. Clinical outcome category was 1 in 2 patients, 2 in 8 patients, and 3 in 2 patients. No patients were in category 4.CONCLUSION: There is a significant and positive correlation between the clinical outcome and the MR imaging score in patients with ANEC. The relation between clinical outcome and each individual MR feature remains to be determined. Patients with ANEC may have a better clinical outcome than has been previously reported.